Ductile Fracture Simulation of Stainless Steel Coupons Under Monotonic Tensile Forces. Issue 4 (14th September 2022) - González‐de‐León, Isabel; Arrayago, Itsaso; Nastri, Elide; Real, Esther
Abstract: Stainless steel alloys exhibit a nonlinear stress‐strain behaviour which can be precisely described by the Ramberg‐Osgood material model up to the ultimate stress. However, there is no consensus on the ductile fracture model under monotonic loading, which affects the post‐necking stress‐strain behaviour, to be adopted for stainless steels, even though the fracture model may have clear applications in structural design, such as in predicting joint failure in direct design approaches. This study presents the calibration of the fracture parameters for two of the most common ductile fracture models: the modified critical stress model and the Lee and Wierzbicki model. The calibrations are based on experimental results from tensile coupons tests on austenitic, ferritic and duplex stainless steel, extracted from cold‐formed tubes and sheet material, and on advanced finite element simulations. The calibrated values show a low dispersion for each of the analysed materials, indicating that the fracture parameters are an inherent property of the material, and which have been found to be slightly higher for the more ductile alloys. Average values of the fracture parameters for different stainless steels are also preliminarily proposed for their direct application in finite element simulations.